Adoption of Evidence-Based Health Promotion Programs: Perspectives of Early Adopters of Enhance®Fitness in YMCA-Affiliated Sites - Belza, Basia; Petrescu-Prahova, Miruna; Kohn, Marlana; Miyawaki, Christina E.; Farren, Laura; Kline, Grace; Heston, Ann-Hilary (Frontiers in Public Health, 2015)
.